High-sensitivity micro-magnetic field giant magneto-impedance sensor material and preparation method and application thereof

By adding Mn, V, Cr, and Mo elements and using single-roller rapid cooling and copper cladding annealing treatment, a high-sensitivity micro-magnetic field giant magnetoimpedance sensor material was prepared, which solved the stability and cost problems of iron-based nanocrystalline alloy materials in high-frequency applications and achieved high-sensitivity and low-cost sensor performance.

CN120784071APending Publication Date: 2025-10-14SHANDONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410422103.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

Existing iron-based nanocrystalline soft magnetic alloy materials have problems such as low Fe content, high cost, complex preparation process and poor stability in high-frequency applications, which limits the development and application of giant magnetoimpedance sensors.

Method used

Using the molecular formula of FeaSibBcCudNbeMf, Mn, V, Cr, and Mo, transition metal elements with large atomic radius, are added. The amorphous alloy strip is prepared by single-roller rapid cooling method, and copper cladding annealing treatment is performed to form a nanocrystalline structure and optimize the soft magnetic properties.

Benefits of technology

The sensitivity and stability of the sensor are improved, the cost is reduced, and excellent soft magnetic properties and high impedance ratio at high frequencies are achieved, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120784071A_ABST
    Figure CN120784071A_ABST
Patent Text Reader

Abstract

The invention provides a high-sensitivity micro-magnetic field giant magneto-impedance sensor material as well as a preparation method and application thereof. The molecular formula of the high-sensitivity micro-magnetic field giant magneto-impedance sensor material is FeaSibBcCudNbeMf, M is a combination of more than two of metal elements Mn, V, Cr and Mo, a, b, c, d, e and f are atomic percentages of corresponding elements, a + b + c + d + e + f = 100, 73 < = a < = 74.5, 12.2 < = b < = 13, 7.2 < = c < = 9.5, 0.5 < = d < = 1, 2.1 < = e < = 2.8, and 0.6 < = f < = 2.5. The invention also provides a preparation method of the material. The GMI sensor material disclosed by the invention has excellent comprehensive soft magnetic performance, and can improve the sensitivity of a sensor and realize the detection of a micro magnetic field when being applied to the GMI sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sensor material preparation, and in particular relates to a high-sensitivity micro-magnetic field giant magneto-impedance sensor material and a preparation method and application thereof. Background Art

[0002] The rapid development of Internet of Things (IoT) technology has driven the development and research of high-performance sensors. Magnetic sensors, as an important branch, are now widely used in automation control, biomedicine, military industry, aerospace, and other fields.

[0003] Commonly used magnetic sensors include Hall effect sensors, fluxgate sensors, giant magnetoresistance sensors, superconducting quantum interference sensors, and giant magnetoimpedance sensors. Giant magnetoimpedance (GMI) is an emerging magnetic sensing technology that offers higher signal output and greater sensitivity to weak magnetic fields than traditional Hall effect sensors and giant magnetoresistance sensors. It also offers lower cost and a smaller size than superconducting quantum interference sensors and fluxgate sensors, and greater portability and lower power consumption than large magnetic field detection systems.

[0004] Since K. Mohri et al. from Nagoya University in Japan discovered the giant magneto-impedance effect in CoFeSiB amorphous wire in 1992, the high sensitivity and fast response speed of amorphous alloy materials to changes in external magnetic fields have made giant magneto-impedance sensors attract widespread attention in the field of magnetic sensors.

[0005] Initially, the most studied materials for giant magnetoimpedance sensors were amorphous cobalt-based soft magnetic alloys with zero or negative magnetostriction coefficients. In order to improve the GMI effect of amorphous alloy materials, domestic and foreign researchers have conducted the following research: (1) using annealing technology to post-process soft magnetic materials; (2) improving the soft magnetic properties of materials by adjusting the chemical composition; (3) using new processes to prepare thin film materials or composite structural materials with different structures.

[0006] Since it is noted that the important factor affecting the GMI effect is the soft magnetic properties of the material, people began to apply iron-based nanocrystalline soft magnetic alloys to the GMI effect research and developed soft magnetic GMI materials with different structures. 73.5 Si 13.5B9Nb3Cu1) nanocrystalline alloys have superior overall soft magnetic properties than silicon steel / Permalloy / ferrite, and are attractive in high-frequency applications. In order to further improve the soft magnetic properties of iron-based nanocrystalline soft magnetic materials, scientific and technological workers have carried out a lot of research. After decades of research and exploration, the current nanocrystalline soft magnetic alloys have mainly developed into four systems: FeSiBMCu (M = Nb, Ta, W, Mo, etc.) series Finemet alloys have the advantages of high μi, low loss, and low cost. They are widely used in high-frequency power electronics and electronic information fields, but their Fe content is low, and the typical composition Bs is only 1.24T, which to a certain extent limits its development and application; FeMB (Cu) (M = Zr, Hf, Nb, etc.) series Nanoperm alloys. This type of nanocrystal has a high Bs (~1.65T) due to its high Fe content (84~90at.%), and also has extremely high μi and excellent frequency characteristics, making it an ideal soft magnetic material for use in high-frequency electronic devices. However, it contains a large amount of precious elements and easily oxidized elements, and needs to be prepared under vacuum conditions, so it has not yet been promoted and applied; (Fe, Co)MBCu (M=Zr, Hf, Nb, etc.) is a Hitperm alloy. The introduction of Co element has successfully developed soft magnetic materials with higher Bs, but the large amount of Co element leads to increased alloy production costs and complex preparation process, making it difficult to promote; FeSiBPCu is a Nanomet alloy. The Bs of this alloy can reach above 1.8T, but the harsh strip preparation and heat treatment process limit the widespread application of this alloy.

[0007] Compared with cobalt-based amorphous alloy materials, iron-based nanocrystalline soft magnetic alloys have lower resistivity, and at the same time have the advantages of high magnetic permeability, low coercive force (Hc) and high saturation magnetic induction intensity (Bs), so the GMI effect is higher. However, currently only Finemet alloy has the ability to be industrialized among the four systems. As mentioned above, the important factor affecting the GMI effect is the soft magnetic properties of the material. Therefore, the development of high-performance soft magnetic alloys is of great significance to the development of GMI sensors.

[0008] Therefore, it is particularly important to seek a nanocrystalline soft magnetic alloy with excellent comprehensive soft magnetic properties. Summary of the Invention

[0009] To address the shortcomings of existing technologies, the present invention provides a highly sensitive micromagnetic field giant magnetoimpedance sensor material, its preparation method, and its application. The giant magnetoimpedance sensor material of the present invention exhibits excellent comprehensive soft magnetic properties. When applied to GMI sensors, it can improve sensor sensitivity and enable detection of micromagnetic fields.

[0010] The technical solutions of the present invention are as follows:

[0011] A high-sensitivity micro-magnetic field giant magneto-impedance sensor material, the molecular formula of the high-sensitivity micro-magnetic field giant magneto-impedance sensor material is: Fe a Si b B c Cu d Nb e M f , M is a combination of two or more of the metal elements Mn, V, Cr, and Mo, wherein a, b, c, d, e, and f are the atomic percentages of the corresponding elements, a+b+c+d+e+f=100, 73≤a≤74.5, 12.2≤b≤13, 7.2≤c≤9.5, 0.5≤d≤1, 2.1≤e≤2.8, and 0.6≤f≤2.5.

[0012] According to a preferred embodiment of the present invention, M is a combination of metal elements Mn and V, and the atomic percentage of Mn and V is 8-15:5-12, more preferably 15:5.

[0013] According to the present invention, the method for preparing the above-mentioned high-sensitivity micro-magnetic field giant magnetoimpedance sensor material comprises the following steps:

[0014] (1) Weighing the raw materials of each element according to atomic percentage and mixing them;

[0015] (2) smelting the mixed material prepared in step (1) in an argon atmosphere to obtain a master alloy ingot; polishing the surface of the master alloy ingot, crushing it, and setting it aside;

[0016] (3) The crushed sample is placed in a quartz tube with a nozzle at the bottom, and a continuous amorphous alloy strip is prepared by a single-roller rapid cooling method;

[0017] (4) The amorphous alloy strip is placed between two copper sheets of the same specifications and fixed with a clamp, and then annealed to obtain a high-sensitivity micro-magnetic field giant magnetoimpedance sensor material.

[0018] According to the preferred embodiment of the present invention, in step (1), the raw materials of elements Si, Cu, Nb, and M are simple substances of the corresponding elements, the raw material of element B is an iron-boron master alloy, and the raw material of element Fe is simple iron and an iron-boron master alloy.

[0019] According to the preferred embodiment of the present invention, the smelting process in step (2) is carried out in vacuum with a vacuum degree of 2-3×10 -3 Pa; melting current is 25-35A; melting times is 3-5 times, each time keeping the molten state for 30-60s.

[0020] According to the preferred embodiment of the present invention, in step (2), the master alloy ingot is obtained by naturally cooling after smelting.

[0021] According to the application, preferably, the size of the broken sample in step (3) is 5-8 mm.

[0022] According to the application, preferably, the melting temperature of the master alloy ingot in step (3) is 1400-1550℃ under argon atmosphere.

[0023] According to the application, preferably, the process parameters of the single-roller rapid quenching method in step (3) are as follows: the spraying pressure is 0.4-0.6 MPa; the melt temperature is 1150-1250℃; and the copper roller rotation speed is 3000-3500 rpm.

[0024] According to the application, preferably, the thickness of the amorphous alloy strip obtained in step (3) is 15-20 μm, and the width is 2-5 mm.

[0025] According to the application, preferably, the length ratio of the amorphous alloy strip to the copper sheet in step (4) is 1:1.2-1.5, the width ratio is 1:4-6, and the thickness ratio is 1:25-35.

[0026] According to the application, preferably, the length and width directions of the amorphous alloy strip in step (4) are parallel to the length and width directions of the copper sheet; and the clamp is not particularly limited, and can be used to fix the strip and the copper sheet, such as a stainless steel push clamp.

[0027] According to the application, preferably, the annealing temperature in step (4) is 400-600℃, the holding time is 1-40 min, the heating rate during the annealing process is 100-120℃ / min, and more preferably, the annealing temperature is 450-550℃, and the holding time is 5-30 min.

[0028] According to the application, the high-sensitivity micro-magnetic field giant magnetoimpedance sensor material is used for preparing a giant magnetoimpedance sensor or a magnetic powder core.

[0029] The technical features and advantages of the application are as follows:

[0030] 1. The high-sensitivity micromagnetic field giant magnetoimpedance sensor material prepared by the present invention incorporates large atomic radius transition metal elements such as Mn, V, Cr, and Mo. This not only increases the mixing enthalpy and atomic mismatch ratio between alloying elements, enhancing the amorphous-forming ability, but also inhibits the growth of nanocrystalline grains. The presence of Mn, V, Cr, and Mo helps to hinder grain growth and stabilize the residual amorphous matrix. Nanocrystals are uniformly distributed on the amorphous matrix, and the nanocrystalline grains are fine, with an average grain size of less than 12 nm. The grain size is effectively controlled, thereby improving the soft magnetic properties. The addition of antiferromagnetic elements such as Mn, V, Cr, and Mo can increase the high-frequency magnetic permeability of the soft magnetic alloy and reduce its high-frequency loss, thereby improving the high-frequency soft magnetic properties of the soft magnetic alloy.

[0031] 2. The high-sensitivity micromagnetic field giant magnetoimpedance sensor material prepared by the present invention has high thermal stability, namely a wide heat treatment temperature range, up to 100°C, and can maintain a coercive force below 1A / m. This effectively reduces temperature control costs while maintaining excellent soft magnetic properties, facilitating industrial production. Furthermore, when the amorphous alloy prepared by the present invention is annealed at the optimal temperature to produce nanocrystals, the nanocrystal grains and the remaining amorphous phase have an optimal volume ratio, and the strongest magnetic coupling interaction exists between the grains and the amorphous phase, resulting in the highest magnetic permeability and lowest coercive force of the nanocrystalline alloy, resulting in an impedance ratio of up to 2475%.

[0032] 3. When the iron-based nanocrystalline soft magnetic alloy prepared by the present invention is used in a giant magneto-impedance sensor, the giant magneto-impedance ratio (ΔZ / Z) can reach up to 2400% or more, and the sensitivity can reach up to 3396% / Oe, with high sensitivity and good stability and linearity. In addition, the present invention adopts a longitudinal drive method. The alternating current of this drive method does not need to pass directly through the sample, which can avoid the contact resistance of the sample lead and the loss caused by the Joule heat of the sample itself. In combination with a DC bias, it can achieve zero-field blind spots. The method is simple and the performance is stable. It does not require other materials to prepare composite strips, which is conducive to mass production. Compared with the cobalt-based amorphous ribbon, which is the most widely used giant magneto-impedance material, it not only has excellent performance, but also has low manufacturing and raw material costs, and has broad market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic diagram of the giant magneto-impedance test of the present invention.

[0034] Figure 2 1 is the XRD curve diagram of the amorphous alloy strip obtained in Example 1-6.

[0035] Figure 3 1 is the XRD curve diagram of the amorphous alloy strip obtained in Comparative Examples 1-5.

[0036] Figure 4The curve of the change rate of the impedance of the giant magneto-impedance sensor material obtained in Example 1 with the change of the magnetic field.

[0037] Figure 5 The curve of the change rate of the impedance of the giant magneto-impedance sensor material obtained in Example 2 with the change of the magnetic field.

[0038] Figure 6 The curve of the change rate of the impedance of the giant magneto-impedance sensor material obtained in Example 3 with the change of the magnetic field.

[0039] Figure 7 The curve of the change rate of the impedance of the giant magneto-impedance sensor material obtained in Example 4 with the change of the magnetic field.

[0040] Figure 8 The curve of the change rate of the impedance of the giant magneto-impedance sensor material obtained in Example 5 with the change of the magnetic field.

[0041] Figure 9 The curve of the change rate of the impedance of the giant magneto-impedance sensor material obtained in Example 6 with the change of the magnetic field.

[0042] Figure 10 The curve of the change rate of the impedance of the giant magneto-impedance sensor material obtained in Comparative Examples 1-5 with the change of the magnetic field. DETAILED DESCRIPTION

[0043] The application is further described below by specific examples, but is not limited to this.

[0044] The materials used in the examples are all conventional materials and can be obtained in the market. The methods are all prior art unless otherwise specified.

[0045] Example 1

[0046] A high-sensitivity micro-magnetic field giant magneto-impedance sensor material, the molecular formula of which is Fe 74.5 Si 12.6 B 7.4 Cu1Nb 2.5 Mn 1. 5V 0.5 .

[0047] The preparation method of the above high-sensitivity micro-magnetic field giant magneto-impedance sensor material, comprising the following steps:

[0048] (1) The raw materials are pure iron (99.99%), pure silicon (99.99%), iron-boron intermediate alloy (boron mass percentage is 17.62%), pure copper (99.99%), pure niobium (99.95%), pure manganese (99.99%), and pure vanadium (99.9%). The raw materials are weighed according to the atomic percentage of Fe, Si, B, Cu, Nb, Mn, and V;

[0049] (2) Put the raw material into a glass tube in a vacuum induction melting furnace, vacuumize to 2x10 -3 Pa, fill in argon for arc melting, the melting current is 30 A, the melting times is 3, each time keep the melting state for 30 s; after melting, naturally cool to get the mother alloy ingot, take out the ingot, clean the surface of the ingot with a file, then break into small ingot pieces (size is 5-8 mm) for melt body tape casting;

[0050] (3) Put the small ingot pieces into a quartz tube with a 1 mm diameter small hole at the bottom end and an inner diameter of 15 mm, place the quartz tube in a high frequency remelting tape casting device, heat to 1450℃, melt, then cast the tape, the spray pressure of the melt is 0.5 MPa, the spray temperature of the melt is 1200℃, the copper roller rotation speed is 3200 rpm, the tape casting process is carried out under argon protection, to get amorphous alloy tape.

[0051] According to the above process, Fe 74.5 Si 12.6 B 7.4 Cu1Nb 2.5 Mn 1.5 V 0.5 amorphous alloy tape, the thickness of the tape is 17 μm, the width is 2.5 mm. Test the phase structure of the quenched state by XRD, as shown in Figure 2 , it presents a completely disordered amorphous structure.

[0052] (4) Cut 30 mm long amorphous alloy tape and place it in the middle of two copper pieces of the same size (the length of the copper piece is 40 mm, the width is 10 mm, and the thickness is 0.5 mm), the length and width directions of the amorphous alloy tape are parallel to the length and width directions of the copper piece, and a stainless steel push clamp is used to fix it, the copper-coated amorphous alloy tape obtained above is placed in a flash annealing furnace with a vacuum system, heated to 520℃ at a heating rate of 100℃ / min, kept for 20 min, then cooled to room temperature with the furnace, and taken out, to get a high sensitivity micro magnetic field giant magneto impedance sensor material.

[0053] Test the initial magnetization curve of the high sensitivity micro magnetic field giant magneto impedance sensor material obtained above by direct current B-H instrument, the initial permeability (μi) of the high sensitivity micro magnetic field giant magneto impedance sensor material prepared in Example 1 is 31847, and the coercive force (Hc) is 0.23 A / m.

[0054] Use the above high sensitivity micro magnetic field giant magneto impedance sensor material to prepare a high sensitivity zero field blind spot giant magneto impedance sensor probe, the specific preparation method is as follows:

[0055] (1) A skeleton (made of photosensitive resin) with a diameter of 4 mm, a length of 30 mm, and an internal groove (the width of the groove is 3 mm and the height is 0.5 mm) was prepared using a light-curing 3D printer.

[0056] (2) A solenoid with a diameter of 3.5 mm was made by tightly winding 100 turns of enameled wire with a diameter of 0.15 mm around the frame prepared in step (1) to serve as the driving coil.

[0057] (3) A bias coil is wound with 150 turns of enameled wire having a diameter of 0.15 mm on the solenoid prepared in step (2).

[0058] (4) Cut 30 mm long pieces of the annealed high-sensitivity micro-magnetic field giant magneto-impedance sensor material and insert them into the groove of the solenoid obtained in step (3), with the giant magneto-impedance sensor material located at the center of the groove. Figure 1 The giant magnetoimpedance sensor probe shown.

[0059] The curve of the impedance change rate of the high-sensitivity giant magneto-impedance sensor material prepared in this embodiment after biasing versus magnetic field is shown in FIG. Figure 4 The driving current amplitude was 10mA and the frequency was 40kHz. The test results are as follows: the maximum giant magneto-impedance ratio of the sample is 2475%, and the sensitivity is 3396% / Oe.

[0060] Example 2

[0061] A highly sensitive micro-magnetic field giant magnetoimpedance sensor material with the molecular formula Fe 74 Si 12.8 B 7.6 Cu 0.8 Nb 2.6 Mn 1.2 V1.

[0062] Fe 74 Si 12.8 B 7.6 Cu 0.8 Nb 2.6 Mn 1.2 The preparation method of the V1 amorphous alloy strip is the same as that in Example 1; the obtained strip has a thickness of 18 μm and a width of 2.5 mm.

[0063] Fe was obtained by XRD test according to the above process. 74 Si 12.8 B 7.6 Cu 0.8 Nb 2.6 Mn 1.2 Phase structure of V1 amorphous alloy strip, such as Figure 2 As shown, the obtained ribbons exhibit a completely disordered amorphous structure.

[0064] The annealing method is the same as that described in Example 1, except that the temperature is raised to 510°C at a heating rate of 100°C / min, kept at that temperature for 20 minutes, and then cooled to room temperature before being taken out.

[0065] The initial magnetization curve of the high-sensitivity micromagnetic field giant magnetoimpedance sensor material obtained above was tested by a DC BH instrument, and it was found that the initial magnetic permeability (μi) of the high-sensitivity micromagnetic field giant magnetoimpedance sensor material obtained in Example 2 was 25477, and the coercive force (Hc) was 0.71 A / m.

[0066] The method for using the above-mentioned high-sensitivity micro-magnetic field giant magneto-impedance sensor material to prepare a high-sensitivity giant magneto-impedance sensor probe without a zero-field blind spot is as described in Example 1.

[0067] The curve of the impedance change rate of the high-sensitivity giant magneto-impedance sensor material prepared in this embodiment after biasing versus magnetic field is shown in FIG. Figure 5 The driving current amplitude was 10mA and the frequency was 40kHz. The test results are as follows: the maximum giant magneto-impedance ratio of the sample is 1722% and the sensitivity is 2966% / Oe.

[0068] Example 3

[0069] A highly sensitive micro-magnetic field giant magnetoimpedance sensor material, whose molecular formula is Fe 74 Si 13 B 8.1 Cu1Nb 2.1 Mn1V 0.8 .

[0070] Fe 74 Si 13 B 8.1 Cu1Nb 2.1 Mn1V 0.8 The preparation method of the amorphous alloy strip is the same as that of Example 1. The obtained strip has a thickness of 17 μm and a width of 2.5 mm.

[0071] Fe was obtained by XRD test according to the above process. 74 Si 13 B 8.1 Cu1Nb 2.1 Mn1V 0.8 The phase structure of the quenched amorphous alloy strip, such as Figure 2 As shown, the obtained ribbons exhibit a completely disordered amorphous structure.

[0072] The annealing method is the same as that described in Example 1, except that the temperature is raised to 515°C at a heating rate of 100°C / min, kept at that temperature for 20 minutes, and then cooled to room temperature and taken out.

[0073] The initial magnetization curve of the high-sensitivity micromagnetic field giant magneto-impedance sensor material obtained above was tested by a DC BH instrument, and it was found that the initial magnetic permeability (μi) of the high-sensitivity micromagnetic field giant magneto-impedance sensor material obtained in Example 3 was 23885, and the coercive force (Hc) was 0.63 A / m.

[0074] The method for using the above-mentioned high-sensitivity micro-magnetic field giant magneto-impedance sensor material to prepare a high-sensitivity giant magneto-impedance sensor probe without a zero-field blind spot is as described in Example 1.

[0075] The curve of the impedance change rate of the high-sensitivity giant magneto-impedance sensor material prepared in this embodiment after biasing versus magnetic field is shown in FIG. Figure 6 The driving current amplitude was 10mA and the frequency was 40kHz. The test results are as follows: the maximum giant magneto-impedance ratio of the sample is 1868%, and the sensitivity is 2976% / Oe.

[0076] Example 4

[0077] A highly sensitive micro-magnetic field giant magnetoimpedance sensor material with the molecular formula Fe 74.5 Si 12.2 B8C 0.8 Nb 2.5 Mn 0. 8V 1.2 .

[0078] Fe 74.5 Si 12.2 B8C 0.8 Nb 2.5 Mn 0.8 V 1.2 The preparation method of the amorphous alloy strip is the same as that of Example 1. The obtained strip has a thickness of 17 μm and a width of 2.5 mm.

[0079] Fe was obtained by XRD test according to the above process. 74.5 Si 12.2 B8C 0.8 Nb 2.5 Mn 0.8 V 1.2 The phase structure of the quenched amorphous alloy strip, such as Figure 2 As shown, the ribbon exhibits a completely disordered amorphous structure.

[0080] The annealing method is the same as that described in Example 1, except that the temperature is raised to 520°C at a heating rate of 100°C / min, kept at that temperature for 20 minutes, and then cooled to room temperature before being taken out.

[0081] The initial magnetization curve of the high-sensitivity micromagnetic field giant magnetoimpedance sensor material obtained above was tested by a DC BH instrument, and it was found that the initial magnetic permeability (μi) of the high-sensitivity micromagnetic field giant magnetoimpedance sensor material obtained in Example 4 was 26273, and the coercive force (Hc) was 0.52 A / m.

[0082] The method for using the above-mentioned high-sensitivity micro-magnetic field giant magneto-impedance sensor material to prepare a high-sensitivity giant magneto-impedance sensor probe without a zero-field blind spot is as described in Example 1.

[0083] The curve of the impedance change rate of the high-sensitivity giant magneto-impedance sensor material prepared in this embodiment after biasing versus magnetic field is shown in FIG. Figure 7 The driving current amplitude was 10mA and the frequency was 40kHz. The test results are as follows: the maximum giant magneto-impedance ratio of the sample is 2188%, and the sensitivity is 2981% / Oe.

[0084] Example 5

[0085] A highly sensitive micro-magnetic field giant magnetoimpedance sensor material with the molecular formula Fe 74 Si 12.6 B 7.7 Cu 0.8 Nb 2.7 Cr1Mo 1.2 .

[0086] Fe 74 Si 12.6 B 7.7 Cu 0.8 Nb 2.7 Cr1Mo 1.2 The preparation method of the amorphous alloy strip is the same as that of Example 1; the obtained strip has a thickness of 18 μm and a width of 2.5 mm.

[0087] Fe was obtained by XRD test according to the above process. 74 Si 12.6 B 7.7 Cu 0.8 Nb 2.7 Cr1Mo 1.2 The phase structure of the quenched amorphous alloy strip, such as Figure 2 As shown, the obtained ribbons exhibit a completely disordered amorphous structure.

[0088] The annealing method is the same as that described in Example 1, except that the temperature is raised to 515°C at a heating rate of 100°C / min, kept at that temperature for 20 minutes, and then cooled to room temperature and taken out.

[0089] The initial magnetization curve of the high-sensitivity micromagnetic field giant magneto-impedance sensor material obtained above was tested by a DC BH instrument, and it was found that the initial magnetic permeability (μi) of the high-sensitivity micromagnetic field giant magneto-impedance sensor material obtained in Example 5 was 23089, and the coercive force (Hc) was 0.87 A / m.

[0090] The method for using the above-mentioned high-sensitivity micro-magnetic field giant magneto-impedance sensor material to prepare a high-sensitivity giant magneto-impedance sensor probe without a zero-field blind spot is as described in Example 1.

[0091] The curve of the impedance change rate of the high-sensitivity giant magneto-impedance sensor material prepared in this embodiment after biasing versus magnetic field is shown in FIG. Figure 8 The driving current amplitude was 10mA and the frequency was 40kHz. The test results are as follows: the maximum giant magneto-impedance ratio of the sample is 1522%, and the sensitivity is 2668% / Oe.

[0092] Example 6

[0093] A high-sensitivity micro-magnetic field giant magnetoimpedance sensor material with a molecular formula of Fe 74 Si 12.8 B 7.6 Cu 0.8 Nb 2.8 Mo 0. 8V 1.2 .

[0094] Fe 74 Si 12.8 B 7.6 Cu 0.8 Nb 2.8 Mo 0.8 V 1.2 The preparation method of the amorphous alloy strip is the same as that of Example 1. The obtained strip has a thickness of 18 μm and a width of 2.5 mm.

[0095] Fe was obtained by XRD test according to the above process. 74 Si 12.8 B 7.6 Cu 0.8 Nb 2.8 Mo 0.8 V 1.2 The phase structure of the quenched amorphous alloy strip, such as Figure 2 As shown, the obtained ribbons exhibit a completely disordered amorphous structure.

[0096] The annealing method is the same as that described in Example 1, except that the temperature is raised to 515°C at a heating rate of 100°C / min, kept at that temperature for 20 minutes, and then cooled to room temperature and taken out.

[0097] The initial magnetization curve of the high-sensitivity micromagnetic field giant magnetoimpedance sensor material obtained above was tested by a DC BH instrument, and it was found that the initial magnetic permeability (μi) of the high-sensitivity micromagnetic field giant magnetoimpedance sensor material obtained in Example 6 was 23526, and the coercive force (Hc) was 0.75 A / m.

[0098] The method for using the above-mentioned high-sensitivity micro-magnetic field giant magneto-impedance sensor material to prepare a high-sensitivity giant magneto-impedance sensor probe without a zero-field blind spot is as described in Example 1.

[0099] The curve of the impedance change rate of the high-sensitivity giant magneto-impedance sensor material prepared in this embodiment after biasing versus magnetic field is shown in FIG. Figure 9 The driving current amplitude was 10mA and the frequency was 40kHz. The test results are as follows: the maximum giant magneto-impedance ratio of the sample is 1567% and the sensitivity is 2716% / Oe.

[0100] Comparative Example 1

[0101] A giant magneto-impedance sensor material, the molecular formula of which is Fe 74 Si 13 B 9.5 Cu 0.8 Nb 2.7 .

[0102] Fe 74 Si 13 B 9.5 Cu 0.8 Nb 2.7 The preparation method of the amorphous alloy strip is the same as that of Example 1. The obtained strip has a thickness of 17 μm and a width of 2.5 mm.

[0103] Fe was obtained by XRD test according to the above process. 75 Si 12 B 9.5 Cu 0.8 Nb 2.7 The phase structure of the quenched amorphous alloy strip, such as Figure 3 As shown, the obtained ribbons exhibit a completely disordered amorphous structure.

[0104] The annealing method is as described in Example 1.

[0105] The initial magnetization curve of the giant magneto-impedance sensor material obtained above was tested by a DC BH instrument, and it was found that the initial magnetic permeability (μi) of the giant magneto-impedance sensor material obtained in Comparative Example 1 was 22810, and the coercive force (Hc) was 0.86 A / m.

[0106] The method for using the above giant magneto-impedance sensor material to prepare a high-sensitivity giant magneto-impedance sensor probe without a zero-field blind spot is as described in Example 1.

[0107] The curve of the impedance change rate of the giant magneto-impedance sensor material prepared in this comparative example as a function of the magnetic field after bias is as follows: Figure 10 The driving current amplitude was 10mA and the frequency was 40kHz. The test results are as follows: the maximum giant magneto-impedance ratio of the sample is 1513% and the sensitivity is 2470% / Oe.

[0108] Comparative Example 2

[0109] A giant magneto-impedance sensor material, the molecular formula of which is Fe 73 Si 12.5 B8Cu1Nb 2.5 Mn2V1.

[0110] Fe 73 Si 12.5 B8Cu1Nb 2.5 The preparation method of the Mn2V1 amorphous alloy strip is the same as that in Example 1. The obtained strip has a thickness of 18 μm and a width of 2.5 mm.

[0111] Fe was obtained by XRD test according to the above process. 73 Si 12.5 B8Cu1Nb 2.5 The phase structure of the quenched Mn2V1 amorphous alloy strip, such as Figure 3 As shown, the obtained ribbons exhibit a completely disordered amorphous structure.

[0112] The annealing method is as described in Example 1.

[0113] The initial magnetization curve of the giant magneto-impedance sensor material obtained above was tested by a DC BH instrument, and it was found that the initial magnetic permeability (μi) of the giant magneto-impedance sensor material prepared in Comparative Example 2 was 23447, and the coercive force (Hc) was 0.84 A / m.

[0114] The method for using the above giant magneto-impedance sensor material to prepare a high-sensitivity giant magneto-impedance sensor probe without a zero-field blind spot is as described in Example 1.

[0115] The curve of the impedance change rate of the giant magneto-impedance sensor material prepared in this comparative example as a function of the magnetic field after bias is as follows: Figure 10 The driving current amplitude was 10mA and the frequency was 40kHz. The test results are as follows: the maximum giant magneto-impedance ratio of the sample is 1475%, and the sensitivity is 2336% / Oe.

[0116] Comparative Example 3

[0117] A giant magneto-impedance sensor material, the molecular formula of which is Fe 74.2 Si 12.3 B8.5 Cu 0.8 Nb 2.7 Mn 1.5 .

[0118] Fe 74.2 Si 12.3 B 8.5 Cu 0.8 Nb 2.7 Mn 1.5 The preparation method of the amorphous alloy strip is the same as that of Example 1. The obtained strip has a thickness of 17 μm and a width of 2.5 mm.

[0119] Fe was obtained by XRD test according to the above process. 74.2 Si 12.3 B 8.5 Cu 0.8 Nb 2.7 Mn 1.5 The phase structure of the quenched amorphous alloy strip, such as Figure 3 As shown, the obtained ribbons exhibit a completely disordered amorphous structure.

[0120] The annealing method is as described in Example 1.

[0121] The initial magnetization curve of the giant magneto-impedance sensor material obtained above was tested by a DC BH instrument, and it was found that the initial magnetic permeability (μi) of the giant magneto-impedance sensor material obtained in Comparative Example 3 was 20820, and the coercive force (Hc) was 1.21 A / m.

[0122] The method for using the above giant magneto-impedance sensor material to prepare a high-sensitivity giant magneto-impedance sensor probe without a zero-field blind spot is as described in Example 1.

[0123] The curve of the impedance change rate of the giant magneto-impedance sensor material prepared in this comparative example as a function of the magnetic field after bias is as follows: Figure 10 The driving current amplitude was 10mA and the frequency was 40kHz. The test results are as follows: the maximum giant magneto-impedance ratio of the sample is 1352% and the sensitivity is 2268% / Oe.

[0124] Comparative Example 4

[0125] A giant magneto-impedance sensor material, the molecular formula of which is Fe 74.5 Si 12.8 B 8.4 Cu1Nb 2.8 Mn 0.3 V 0.2 .

[0126] Fe 74.5 Si 12.8 B 8.4 Cu1Nb2.8 Mn 0.3 V 0.2 The preparation method of the amorphous alloy strip is the same as that of Example 1. The obtained strip has a thickness of 18 μm and a width of 2.5 mm.

[0127] Fe was obtained by XRD test according to the above process. 74.5 Si 12.8 B 8.4 Cu1Nb 2.8 Mn 0.3 V 0.2 The phase structure of the quenched amorphous alloy strip, such as Figure 3 As shown, the obtained ribbons exhibit a completely disordered amorphous structure.

[0128] The annealing method is as described in Example 1.

[0129] The initial magnetization curve of the giant magneto-impedance sensor material obtained above was tested by a DC BH instrument, and it was found that the initial magnetic permeability (μi) of the giant magneto-impedance sensor material obtained in Comparative Example 3 was 19203, and the coercive force (Hc) was 0.99 A / m.

[0130] The method for using the above giant magneto-impedance sensor material to prepare a high-sensitivity giant magneto-impedance sensor probe without a zero-field blind spot is as described in Example 1.

[0131] The curve of the impedance change rate of the giant magneto-impedance sensor material prepared in this comparative example as a function of the magnetic field after bias is as follows: Figure 10 The driving current amplitude was 10mA and the frequency was 40kHz. The test results are as follows: the maximum giant magneto-impedance ratio of the sample is 1339% and the sensitivity is 2198% / Oe.

[0132] Comparative Example 5

[0133] A giant magneto-impedance sensor material, the molecular formula of which is Fe 74.5 Si 12.6 B 7.4 Cu1Nb 2.5 Mn 1.5 V 0.5 .

[0134] Fe 74.5 Si 12.6 B 7.4 Cu1Nb 2.5 Mn 1.5 V 0.5 The preparation method of the amorphous alloy strip is the same as that of Example 1. The obtained strip has a thickness of 17 μm and a width of 2.5 mm.

[0135] Fe was obtained by XRD test according to the above process. 74.5 Si12.6 B 7.4 Cu1Nb 2.5 Mn 1.5 V 0.5 The phase structure of the quenched amorphous alloy strip, such as Figure 3 As shown, the resulting amorphous structure is completely disordered.

[0136] The annealing method is as follows: cut a 30mm long amorphous alloy strip, place the strip neatly in a flash annealing furnace with a vacuum system, heat it to 520℃ at a heating rate of 100℃ / min, keep it warm for 20 minutes, then cool it to room temperature and take it out to obtain the giant magnetoimpedance sensor material.

[0137] The initial magnetization curve of the giant magneto-impedance sensor material obtained above was tested by a DC BH instrument, and it was found that the initial magnetic permeability (μi) of the giant magneto-impedance sensor material prepared in Comparative Example 3 was 25135, and the coercive force (Hc) was 0.7 A / m.

[0138] The method for using the above giant magneto-impedance sensor material to prepare a high-sensitivity giant magneto-impedance sensor probe without a zero-field blind spot is as described in Example 1.

[0139] The curve of the impedance change rate of the giant magneto-impedance sensor material prepared in this comparative example as a function of the magnetic field after bias is as follows: Figure 10 The driving current amplitude was 10mA and the frequency was 40kHz. The test results are as follows: the maximum giant magneto-impedance ratio of the sample is 1756%, and the sensitivity is 2941% / Oe.

[0140] Table 1 shows the test results of Examples 1-6 and Comparative Examples 1-5 From the comparison of Comparative Examples 1 and 3 with Examples 1-6 in Table 1, it is not difficult to find that when two or more elements of the metal elements Mn, V, Cr, and Mo are added in combination, the soft magnetic properties of the nanocrystalline alloy are greatly improved compared to Comparative Example 1 in which no metal elements such as Mn, V, Cr, and Mo are added and Comparative Example 3 in which only one such metal element is added. Since the giant magneto-impedance effect is positively correlated with the soft magnetic properties of the material, the maximum impedance ratio and sensitivity characterizing the giant magneto-impedance effect are also high. It can be seen from Comparative Examples 2 and 4 that, compared with Examples 1-6, when the atomic percentage of the combination of two or more elements of the metal elements Mn, V, Cr, and Mo exceeds 2.5 and is less than 0.6, the soft magnetic properties of the nanocrystalline soft magnetic alloy show a downward trend, and the maximum impedance ratio and sensitivity of the test also show a downward trend. Therefore, the optimal percentage of the combination of Mn, V, Cr, and Mo is between 0.6 and 2.5.

[0141] From the comparison between Comparative Example 5 and Example 1, it is not difficult to find that the amorphous ribbons with the same composition have greatly improved soft magnetic properties and giant magneto-impedance effect by adopting copper cladding annealing heat treatment compared with heat treatment without copper cladding.

[0142] As can be seen from Examples 5 and 6, in terms of the combined addition effects of Mn, V, Cr, and Mo, the soft magnetic properties and giant magneto-impedance effects of the nanocrystalline ribbons prepared by the Cr and Mo addition combination of Example 5 and the Mo and V addition combination of Example 6, as well as any other two element combinations, are superior to the nanocrystalline ribbons prepared by Comparative Examples 1-3, which do not add any or only add one or add more than 2.5 of these metal elements. However, it is undeniable that the nanocrystalline ribbons prepared by Examples 5 and 6 have a certain gap in both soft magnetic properties and giant magneto-impedance effects compared to Examples 1-4. The atomic percentages of Mn and V in Examples 1-4 are (8-15):(5-12). Based on the above composition and the ratio of Mn to V, the present invention believes that when the combined addition amount of Mn and V does not exceed 2.5 atomic percent and the atomic percentages of Mn and V added are between (8-15):(5-12), relatively excellent nanocrystalline soft magnetic properties and, thus, a larger giant magneto-impedance effect can be obtained. When the atomic percentage of Mn to V is 15:5, the soft magnetic properties and giant magneto-impedance effect are the best, the maximum initial permeability can reach 31847, the maximum impedance ratio is 2475% at 40KHz, and the sensitivity is as high as 3396% / Oe.

[0143] In summary, the appropriate addition of large atomic radius transition metal elements such as Mn, V, Cr, and Mo, especially the combined addition of Mn and V, can increase the mixing enthalpy and atomic mismatch ratio between alloying elements, thereby improving the glass-forming ability of amorphous alloys. Combined with optimal heat treatment conditions, the optimal crystallized volume fraction can be achieved, resulting in the strongest magnetic coupling interaction between the grains and the amorphous phase, endowing nanocrystalline soft magnetic alloys with excellent soft magnetic properties. When used in giant magnetoimpedance sensors, this can improve the maximum impedance ratio and sensor sensitivity.

[0144] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Various modifications and variations are possible for those skilled in the art. Any modifications and improvements made within the scope of the principles of the present invention shall be included within the scope of protection of the present invention.

Claims

1. A high-sensitivity micro-magnetic field giant magneto-impedance sensor material, characterized in that: The molecular formula of the high-sensitivity micro-magnetic field giant magneto-impedance sensor material is: Fe a Si b B c Cu d Nb e M f , M is a combination of two or more of the metal elements Mn, V, Cr, and Mo, wherein a, b, c, d, e, and f are the atomic percentages of the corresponding elements, a+b+c+d+e+f=100, 73≤a≤74.5, 12.2≤b≤13, 7.2≤c≤9.5, 0.5≤d≤1, 2.1≤e≤2.8, and 0.6≤f≤2.

5.

2. The high-sensitivity micro-magnetic field giant magneto-impedance sensor material according to claim 1, characterized in that: The M is a combination of metal elements Mn and V, and the atomic percentage of Mn and V is 8-15:5-12, preferably 15:

5.

3. The method for preparing the high-sensitivity micro-magnetic field giant magneto-impedance sensor material according to claim 1 or 2, characterized in that: The steps are as follows: (1) Weighing the raw materials of each element according to atomic percentage and mixing them; (2) Evenly melting the mixed material prepared in step (1) in a high-purity argon atmosphere to obtain a master alloy ingot; polishing and crushing the master alloy ingot for later use; (3) The crushed sample is placed in a quartz tube with a nozzle at the bottom, and a continuous amorphous alloy strip is prepared by a single-roller rapid cooling method; (4) The amorphous alloy strip is placed between two copper sheets of the same specifications and fixed with a clamp, and then annealed to obtain a high-sensitivity micro-magnetic field giant magnetoimpedance sensor material.

4. The method for preparing a high-sensitivity micro-magnetic field giant magneto-impedance sensor material according to claim 3, characterized in that: In step (1), the raw materials of the elements Si, Cu, Nb, and M are simple substances of the corresponding elements, the raw material of the element B is an iron-boron master alloy, and the raw materials of the element Fe are simple iron and an iron-boron master alloy.

5. The method for preparing a high-sensitivity micro-magnetic field giant magneto-impedance sensor material according to claim 3, characterized in that: The smelting process in step (2) is carried out in vacuum with a vacuum degree of 2-3×10 -3 Pa; the smelting current is 25-35A; the smelting times are 3-5 times, and each time the molten state is maintained for 30-60s; after smelting, the master alloy ingot is obtained by natural cooling.

6. The method for preparing a high-sensitivity micro-magnetic field giant magneto-impedance sensor material according to claim 3, characterized in that: The size of the crushed sample in step (3) is 5-8 mm; In step (3), the master alloy ingot is melted in an argon atmosphere at a melting temperature of 1400-1550°C; the process parameters of the single-roller rapid cooling strip spinning method are: injection pressure of 0.4-0.6MPa; melt temperature of 1150-1250°C; and copper roller speed of 3000-3500 rpm.

7. The method for preparing a high-sensitivity micro-magnetic field giant magneto-impedance sensor material according to claim 3, characterized in that: In step (4), the length ratio of the amorphous alloy strip to the copper sheet is 1:1.2-1.5, the width ratio of the amorphous alloy strip to the copper sheet is 1:4-6, and the thickness ratio of the amorphous alloy strip to the copper sheet is 1:25-35.

8. The method for preparing a high-sensitivity micro-magnetic field giant magneto-impedance sensor material according to claim 3, characterized in that: The length and width directions of the amorphous alloy strip in step (4) are parallel to the length and width directions of the copper sheet, respectively.

9. The method for preparing a high-sensitivity micro-magnetic field giant magneto-impedance sensor material according to claim 3, characterized in that: The annealing temperature in step (4) is 400-600°C, and the holding time is 1-40 min; the heating rate of the annealing process is 100-120°C / min; preferably, the annealing temperature is 450-550°C, and the holding time is 5-30 min.

10. Use of the high-sensitivity micro-magnetic field giant magneto-impedance sensor material according to claim 1 or 2, characterized in that: Used to prepare giant magnetoimpedance sensors or magnetic powder cores.